2019
DOI: 10.1016/j.rmed.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue disease-associated interstitial lung disease and outcomes after hospitalization: A cohort study

Abstract: Background: The impact of hospitalization on patient outcomes is increasingly recognized and considered in the prognostication of many pulmonary disorders. We sought to evaluate the impact of hospitalization on survival in connective tissue disease-interstitial lung disease (CTD-ILD) patients. Methods: A chart review of patients with CTD-ILD followed at a tertiary care center was performed. Patients were stratified into two groups based on hospitalization status. Outcomes of the groups were compared using Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
2
11
1
Order By: Relevance
“…However, at the time of hospitalization, the differences in VC and DLCO between IPF and non-IPF patients had disappeared. As can be seen in E- Table 2, in comparison with most other studies, here the median time from diagnosis to hospitalization seemed to be longer [5,6,9] and patients were older [5][6][7]9], even though the baseline pulmonary function test (PFT) values in our study and those of others were approximately at the same level. A Japanese study has reported the PFT results of the investigated subjects near the rst hospitalization date were higher than in our material, even though the patients in that study and our own were approximately the same age [11].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, at the time of hospitalization, the differences in VC and DLCO between IPF and non-IPF patients had disappeared. As can be seen in E- Table 2, in comparison with most other studies, here the median time from diagnosis to hospitalization seemed to be longer [5,6,9] and patients were older [5][6][7]9], even though the baseline pulmonary function test (PFT) values in our study and those of others were approximately at the same level. A Japanese study has reported the PFT results of the investigated subjects near the rst hospitalization date were higher than in our material, even though the patients in that study and our own were approximately the same age [11].…”
Section: Discussionsupporting
confidence: 52%
“…Most of the register-based studies have investigated solely patients with IPF, while those of other ILDs are sparse. Table 1 presents data from previously published epidemiological studies and real-world data (RWD) studies on hospitalizations of ILD patients [5][6][7][8][9][10][11]. Table 1 here Acute exacerbation (AE) is a severe complication of ILD, which seems to cause signi cant mortality in all types of ILDs [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the register-based studies have investigated solely patients with IPF, while those of other ILDs are sparse. Table 1 presents data from previously published epidemiological studies and other studies on hospitalizations of ILD patients [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies with access to the patient data, the proportion of AE-ILDs out of all the hospitalizations caused by an acute respiratory deterioration has ranged between 29-55% [5,6,10,11], when only two of these investigations included patients with non-IPF ILDs [5,11]. In the previous studies, which have not presented the exact data on the number of AE-ILDs, it was claimed that respiratory or cardiopulmonary hospitalizations increased the mortality of ILD patients more than hospitalization due to other illnesses [7,9].…”
Section: Introductionmentioning
confidence: 99%